(untitled) (Praxis Educativa, 2012)
We agree with Gloria Ladson-Billings (1999) that the moral and ethical dimensions of teaching constitute “the missing entry” in educational portfolios. Nevertheless, years of experience in the implementation of such an instument of alternative assessment – continuous, formative and process-centred- in the subject English Language II at the Univrsity of La Pampa s English Teacher Training College caused our inquiries to be focused on the above dimensions. From an outlook on teaching and evaluation as humanistic, epistemological and ethical, in which our teaching and assessment practices are subjected to permanent scrutiny following the paradigm of participatory Action-Research, educating in values constitutes a component without which our work would lack sense and perspective. But, improved classes and assessment instruments are not enough for the betterment of students as integral educational subjects. The present work shows how, working with portfolios in a propitious context, students become assessors, redistributing and democratizing the exercising of a such a role, and develop attitudes of responsibility, reflection, self-criticism, cooperation, commitment, solidarity, tolerance and acceptance and integration of differences. We hold this genuinely means educating in values and contribute to the training of human resources professionally and ethically prepared to foster educational, social and moral change.